Sevoflurane Promotes Neurodegeneration Through Inflammasome Formation in APP/PS1 Mice - Li, Guohua; Wang, Yu; Cao, Fang; Wang, Dawei; Zhou, Limin; Jin, Yanwu (Frontiers in Neuroscience, 2021)
Sevoflurane (SEVO) is a highly fluorinated methyl isopropyl ether used as an inhalational anesthetic for general anesthesia. Previous studies have shown that SEVO may induce impaired memory and recognition ability, and may be associated with neurodegenerative disease, e.g. Alzheimer’s disease (AD). However, the underlying mechanism remains unknown. Here, we used a mouse AD model, APP/PS1, to study the effects of SEVO on neurodegeneration. We found that SEVO exposure significantly impaired the spatial reference memory, sensorimotor and cognitive function of the mice. Mechanistically, we found that SEVO induced formation of NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome and its downstream caspase 1-mediated production of IL-1β and IL-18, which subsequently deactivated brain-derived neurotrophic factor (BDNF) to promote neurodegeneration. Together, these data suggest that NLRP3 inflammasome is essential for SEVO-induced neurodegeneration.